Biochemical and pharmacological effects of the direct thrombin inhibitor AR-H067637 - Deinum, Johanna; Mattsson, Christer; Inghardt, Tord; Elg, Margareta (Thrombosis and haemostasis, 2009)
AZD0837 is in development as a new oral anticoagulant for use in thromboembolic disorders. In vivo, AZD0837 is converted to AR-H067637, a selective and reversible direct thrombin inhibitor. Established biochemical methods were used to assess and measure the biochemical and pharmacological properties of AR-H067637. Both direct Biacore binding studies of AR-H067637 with immobilised alpha-thrombin and inhibition studies using pre-steady state kinetics with thrombin in the fluid phase confirmed that AR-H067637 is a rapid-binding, reversible and potent (inhibition constant K(i) = 2-4 nM), competitive inhibitor of thrombin, as well as of thrombin bound to fibrin (clot-bound thrombin) or to thrombomodulin. The total amount of free thrombin generated in platelet-poor clotting plasma was inhibited concentration-dependently by AR-H067637, with a concentration giving half maximal inhibition (IC(50)) of 0.6 microM. Moreover, AR-H067637 is, with the exception of trypsin, a selective inhibitor for thrombin without inhibiting other serine proteases involved in haemostasis. Furthermore, no anticoagulant effect of the prodrug was found. AR-H067637 prolonged the clotting time concentration-dependently in a range of plasma coagulation assays including activated partial thromboplastin time, prothrombin time, prothrombinase-induced clotting time, thrombin time and ecarin clotting time. The two latter assays were found to be most sensitive for assessing the anticoagulant effect of AR-H067637 (plasma IC(50) 93 and 220 nM, respectively). AR-H067637 also inhibited thrombin-induced platelet activation (by glycoprotein IIb/IIIa exposure, IC(50) 8.4 nM) and aggregation (IC(50) 0.9 nM). In conclusion, AR-H067637 is a selective, reversible, competitive inhibitor of alpha-thrombin, with a predictable anticoagulant effect demonstrated in plasma coagulation assays.